Exploring the Barriers and Enablers to the Use of Open Educational Resources by University Academics in Africa - (:unkn) unknown (My University, 2012)
Considerable effort has gone into Open Educational Resource (OER) initiatives in the past decade. These initiatives have created free, high quality educational resources for everyone and anyone to use. However, these open and free resources appear to remain largely unused by university academics on the educationally resource-poor African continent. The objectives of the research study are to explore the inhibitors and enablers are experienced by academics that use OER, and what barriers prevent academics from using OER. The sample consists of academics from East, West and Southern Africa. Information was gathered by means of a survey questionnaire. A modified version of the Unified Theory of Acceptance and Use of Technology model was used to identify the influence of certain factors on a user’s intention to adopt OER. Some of the key findings indicate that Performance Expectancy and Effort Expectancy have a positive effect on a user’s Behavioural Intention to use OER, and the latter has a strong influence on the Actual Use of OER. Facilitating Conditions do not have a statistically significant impact. Additionally, significant differences were found in the barriers which users and potential users of OER have identified as either limiting their current use of OER, or negatively affecting their intention to use OER. These barriers include discovery, relevance, context and individual resources. Addressing these factors could lead to a more widespread adoption of Open Educational Resources in Africa and, consequently, more pervasive and higher quality educational opportunities.
Keywords: African Research